2015
DOI: 10.3892/etm.2015.2172
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of novel (-)-gossypol nanoparticles and the effect on growth inhibition in human prostate cancer PC-3 cells in vitro

Abstract: The aim of the present study was to investigate the antitumor effects and possible mechanism of (-)-gossypol nanoparticles, loaded with vv polyethylene glycol-maleimide (mPEG-Mal), in vitro. Emulsification-volatilization was used to prepare the loaded (-)-gossypol nanoparticles. The toxicity of blank nanoparticles on human prostate cancer PC-3 cells and human prostate RWPE-1 cells was measured. The antitumor effects of the nanoparticles on PC-3 cells were evaluated by an MTT assay, acridine orange staining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…These results are in good accordance with previous published ones showing that a sequentially applied or combined TMZ+AT101/single AT101 treatment was highly efficient and showed an inhibition of GBM proliferation. , Here, TMZ and AT101 are mechanistically different, synergistically acting drugs . While the therapeutic benefit of TMZ depends on its ability to alkylate/methylate DNA most frequently at the N-7 or O-6 positions of guanine residues, AT101 competitively binds to hydrophobic surface grooves of pro-survival Bcl-2 family members, counteracting their protective effects and facilitating apoptosis in tumor cells, and is also able to trigger autophagic cell death. , Recently, to further improve the anti-cancer potential of AT101, liposome-based delivery of gossypol has been used. Interestingly, these nanoparticle approaches with AT101-loaded liposomes, micelles, or polymeric capsules were not able to show increased cytotoxicity of encapsulated compared to free drug in prostate, ovarian, and breast cancer cell lines. ,,, Complementing these results, we demonstrated tunable AT101 release from the 3D microchannel matrices, inducing significant anti-tumorigenic effects in human GBM cell lines whilst leaving the human astrocytes largely unaffected. In the next step, the demonstrated treatment scheme could be adapted to in vivo studies.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in good accordance with previous published ones showing that a sequentially applied or combined TMZ+AT101/single AT101 treatment was highly efficient and showed an inhibition of GBM proliferation. , Here, TMZ and AT101 are mechanistically different, synergistically acting drugs . While the therapeutic benefit of TMZ depends on its ability to alkylate/methylate DNA most frequently at the N-7 or O-6 positions of guanine residues, AT101 competitively binds to hydrophobic surface grooves of pro-survival Bcl-2 family members, counteracting their protective effects and facilitating apoptosis in tumor cells, and is also able to trigger autophagic cell death. , Recently, to further improve the anti-cancer potential of AT101, liposome-based delivery of gossypol has been used. Interestingly, these nanoparticle approaches with AT101-loaded liposomes, micelles, or polymeric capsules were not able to show increased cytotoxicity of encapsulated compared to free drug in prostate, ovarian, and breast cancer cell lines. ,,, Complementing these results, we demonstrated tunable AT101 release from the 3D microchannel matrices, inducing significant anti-tumorigenic effects in human GBM cell lines whilst leaving the human astrocytes largely unaffected. In the next step, the demonstrated treatment scheme could be adapted to in vivo studies.…”
Section: Resultssupporting
confidence: 91%
“…60−62 Interestingly, these nanoparticle approaches with AT101-loaded liposomes, micelles, or polymeric capsules were not able to show increased cytotoxicity of encapsulated compared to free drug in prostate, ovarian, and breast cancer cell lines. 60,61,63,64 Complementing these results, we demonstrated tunable AT101 release from the 3D microchannel matrices, inducing significant anti-tumorigenic effects in human GBM cell lines whilst leaving the human astrocytes largely unaffected. In the next step, the demonstrated treatment scheme could be adapted to in vivo studies.…”
Section: ■ Results and Discussionsupporting
confidence: 61%
“…Interestingly, nanoparticle approaches employing AT101 loaded into liposomes, micelles or polymeric capsules did not show an increased cytotoxicity of the encapsulated compared with free drug in prostate, ovarian or breast cancer cell lines. 23 , 24 , 59 , 60 To our knowledge, no such studies focusing on GBM cells have yet been conducted. Exceptional tumor-growth control was established by multi-drug stimulation and functionalization of nanoparticles for targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Another report focused on polymeric nanoparticles made from methoxypolyethylene glycol-maleimide (mPEG-Mal) and gossypol. 24 The nanoparticles exhibited a favorable anti-cancer activity in human prostate cancer PC-3 cells via induction of apoptosis, with no toxicity of blank samples in a concentration comparable to that of the free drug. Another approach involved the use of gossypol-capped mitoxantrone-loaded mesoporous SiO 2 nanoparticles for the coordinated and controlled release of two anti-cancer drugs.…”
Section: Introductionmentioning
confidence: 95%
“…Previously, (-)-gossypol-loaded cubosomes and polymeric nanoparticles were investigated, respectively. 20 , 21 Both of the two preparations showed effective tumor cell inhibition in vitro, but the drug efficacy in vivo was not clear. Tomoda et al reported an injectable (-)-gossypol-loaded Pluronic P85 micelle which had limited antitumor efficacy alone but could significantly enhance the antitumor efficacy of radiation therapy.…”
Section: Introductionmentioning
confidence: 99%